META-ANALISIS COOPERATIVE LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN IPA/ FISIKA SISWA - Syafrial Syafrial (Journal of Teaching and Learning Physics, 2018)
This meta-analysis aims to summarize the results of research on the effect of cooperative learning to improve students' critical thinking skills so that it can be seen: the average effect size (ES), the type of CL which has the largest and consistent effect size (ES) critical students. The research method used is descriptive with the form of survey research. The number of research results summarized is 19 journal articles. The results of the data analysis resulted in an ES of 0.71. (contributing 26, 32%). The type of cooperative learning that produces the greatest and most consistent influence is the Basic Learning Type Problem (ES = 1.08, contributing 17.97%). At the level of education CL the contribution is large at the high school level, namely (ES = 0.79, contributing 35.33%).